Hipertexto e Groupware: diretrizes para a criação da rede virtual de aprendizagem PPGCI.NET do Programa de Pós-Graduação em Ciência da Informação-UFPB - Leandro, Heloísa Cristina da Silva (2010)
The need for information organization imposed by the increasing informational bulk rouses treatment measures by professionals among the most diverse information systems, such as archives, libraries, documentation centers, museums, and others. In society, nowadays, the exarcebated volume of the connective input of social, cultural, economic and technological wealth, which refers to information, requires that countries promote measures that go far beyond the physical space found in such systems so as to get into the virtual world. Intellectual technologies, then, come into action as a solution concerning the increasing informational flow, among them, the digital hypertext as a technology for the organization, management as well as communication of informational blocks; and groupware blog, chat and discussion lists as those ones capable of stimulating users to both individual and collective intelligence in the context of virtual learning nets. The overall aim is directed to the analysis of the digital hypertext as a technology targeted on information management and organization in the perspective of information communication. The specific ones cover the creation of a study group involving professors, researchers and Master students on areas like Management, Computer Science and Information Science, with the purpose of discussing interdisciplinary relations; the elaboration of guidelines for the production of the Virtual Learning Net's prototype PPGCI.NET, of the Postgraduate Program on Information Science/UFPB, by means of the relation digital hypertext -groupware blog, chat and discussion list; and the investigation into digital hypertext in the perspective of organization and management for information communication as regards to the guidelines for the development of the Virtual Learning Net PPGCI.NET. The methodological features as to method types, research, objective, gathering procedures and data nature correspond, respectively, to the following ones: research-action method, practical research or research-action, participant research, exploratory research and qualitative one. The substantiated plurality of theoretical voices - throughout the research - also includes the methodological analysis of the Hypertextus Study Group's discussions, of the students' - the ones who are representative of the Postgraduate Program on Information Science/UFPB, and of the volunteered participation of an Information Science professional. The aspects, described above, represent only some links of such an untiring web of investigation called hypertext.